Heat transfer and friction factor of water based TiO2 and SiO2 nanofluids under turbulent flow in a tube - Azmi, W.H. (Elsevier Ltd, 2014)
The heat transfer coefficient and friction factor of TiO2 and SiO2 water based nanofluids flowing in a circular tube under turbulent flow are investigated experimentally under constant heat flux boundary condition. TiO2 and SiO2 nanofluids with an average particle size of 50nm and 22nm respectively are used in the working fluid for volume concentrations up to 3.0. Experiments are conducted at a bulk temperature of 30Â°C in the turbulent Reynolds number range of 5000 to 25,000. The enhancements in viscosity and thermal conductivity of TiO2 are greater than SiO2 nanofluid. However, a maximum enhancement of 26 in heat transfer coefficients is obtained with TiO2 nanofluid at 1.0 concentration, while SiO2 nanofluid gave 33 enhancement at 3.0 concentration. The heat transfer coefficients are lower at all other concentrations. The particle concentration at which the nanofluids give maximum heat transfer has been determined and validated with property enhancement ratio. It is observed that the pressure drop is directly proportional to the density of the nanoparticle. Â© 2014 Elsevier Ltd.